The vicious cycle towards violence: focus on the negative feedback mechanisms of brain serotonin neurotransmission - De Boer, Sietse; Caramaschi, Doretta; Natarajan, Deepa; Koolhaas, Jaap (Frontiers in Behavioral Neuroscience, 2009)
Violence can be defined as a form of escalated aggressive behavior that is expressed out of context and out of inhibitory control, and apparently has lost its adaptive function in social communication. Little is known about the social and environmental factors as well as the underlying neurobiological mechanisms involved in the shift of normal adaptive aggression into violence. In an effort to model the harmful acts of aggression and violence in humans, we recently (re)developed an animal model that is focused on engendering uncontrolled forms of maladaptive aggressive behavior in laboratory-bred feral rats and mice. We show that certain (8-12%) constitutionally aggressive individuals gradually develop, over the course of repetitive exposures to victorious social conflicts, escalated (short-latency, high-frequency and ferocious attacks), persistent (lack of attack inhibition by defeat/submission signals and perseverance of the aggressive attack-biting bout), indiscriminating (attacking female and anesthetized male intruders) and injurious (enhanced vulnerable-body region attacks and inflicted wounding) forms of offensive aggression. Based on the neurobiological results obtained using this model, a revised view is presented on the key role of central serotonergic (auto)regulatory mechanisms in this transition of normal aggression into violence.